Haze Modelling and Simulation in Remote Sensing Satellite Data - Asmala, A.; Shaun, Quegan (HIKARI LTD, 2014)
In atmospheric haze studies, it is almost impossible to obtain remote sensing data which have the required haze concentration levels. This problem can be overcome if we can generate haze layer based on the properties of real haze to be integrated with remote sensing data. This work aims to generate remote sensing datasets that have been degraded with haze by taking into account the spectral and spatial properties of real haze. Initially, we modelled solar radiances observed from satellite by taking into consideration direct and indirect radiances reflected from the Earth surface during hazy condition. These radiances are then simulated using the 6SV1 radiative transfer model so that the radiances due to haze, or the so called ‘haze layer’, can be computed. The spatial distribution of the haze layer is simulated based on multivariate Gaussian distribution. The haze layer is finally added to a real dataset to produce a hazy dataset. The generated hazy datasets are to be used in investigating the effects of haze on land cover classification in the future.